The challenges of wireless internet access in vehicular environments - Abakar, Mahamat Ahmat; Saeed, Rashid. A.; Hassan Abdalla Hashim, Aisha; Mohammed, Omer M.; Khalifa, Othman Omran; Islam, Shayla (2010)
The economics of currently available broadband access technologies motivate for innovate and deploy new system designs and applications in vehicular communication. The widely available and flexible Wi-Fi technique meets the cost and suitability targets for vehicular applications. To cope with the special requirements of vehicular, amendments of 802.11 standards at the MAC and PHY protocol level has been introduced in IEEE802.11p. IEEE 802.11p is the proposed standard for physical and MAC layer of wireless access in vehicular environment (WAVE) devices. The main objective of the new standard is to amend 802.to support vehicle mobility up to 150km/hr and distance 1000km by changing the frame format and increase delay spread tolerance introduced, in which the channel bandwidth is scaled from 20 MHz in 802.11a to 10 MHz in 802.11p. This paper reviews the challenges of wireless internet connectivity in vehicular communication. Transmission range, data handover and security are also covered in the paper. Other related works is reviewed and analyzed as well.